14th - 16th centuries Grand Duchy of Lithuania border Pacts and delimitation procedures - Čelkis, Tomas (Lietuvos istorijos studijos, 2010)
This article analyzes Grand Duchy of Lithuania (forward GDL) frontiers treaties and their practice - frontier marking process in 14th-16th century. State territory conception in GDL, which stimulated the beginning of frontiers delimitation, is under consideration as well. This article sifts through the State frontiers evaluating documents, pointing out some groups of them. Separate part of the article discuss frontiers determination process, State delimitation projects arrangement circumstances, the convention and conference organization of State ambassadors. The other part is up for State ambassadors (negotiators) board constitution, their functions; treaty formation and confirmation by oath and stamp ceremony. However, technical side of the frontiers marking, denotation and limitation processes are also pointed out. On the whole, this research article will help to realize GDL State conception development procedure, highlight some international law accents into the context of the territory.
Keywords: -